Perception of beneficiaries towards adoption of e-money in the distribution of social assistance in Indonesia - Sartika Djamaluddin; Achmad Nizar Hidayanto; Sita Wardhani (Economic Journal of Emerging Markets, 2016)
Wide access to formal finance for poor households through distribution of social assistance via electronic money (E-money) is believed to accelerate eradication of poverty. We would like to find out the beneficiaries response to this payment method. This aims of this study is to investigate the perception of beneficiaries towards distribution of social assistance through e-money. We surveyed 230 beneficiaries in Jakarta, Cirebon and Pasuruan. The result of research indicates that the perception of PKH beneficiaries related to the cost, benefits and security of e-money is relatively good. However, from the aspect of ease of use and the respondents’ desire to use e-money, the perception is quite low.